The Channel Management of Enjoy Semarang in Tribun Jateng News Website - Shela Kusumaningtyas; S. Rouli Manalu, Ph.D (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Tribun Jateng Newspaper has its official website, jateng.tribunnews.com. It is built as the media convergence. On the website, there is a section called Enjoy Semarang. This section should focus on the travel news. As for its management, Enjoy Semarang section could not attract a lot of visitors. Based on the observation, the visitors of this section per month is only around 1,392. The news appearing on the website also covers the news of another region and abroad, and this is not appropriate with the name of the section. Not all published reports were written by reporters. There is some news which is adapted from foreign news websites or copied from websites coming from the same company group. None reporters deal with this section specifically. We have worked with Tribun Jateng to manage this section. The objective of this study is to provide the latest news and information about Central Java culinary, travel, and tips through accessible website. Moreover, we have handled the editorship management in the online media and the policy with regard to the selection of the news. The accumulative total of Tribun Jateng Travel visitors for two months is 13,000, exceeding the minimum target which is 4,329. In a day, the minimum obtained traffic is 900. The total of published articles for two months is 316 news, exceeding the minimum target, 300 articles. The published articles are fulfilled the editorial criteria and proper with the topics. Tribun Jateng Travel section has great potential to compete with hard news section. The quality and quantity of the content must be considered as priority. The increase of the traffic should be followed by the adherence of the rules of journalistic writing.